DIGITALISASI MEDIA BELAJAR UNTUK MENINGKATKAN LITERASI DIGITAL SISWA KELAS VII MTs - Rizqiya, Nur Wahyu; Pebri Setiani, Puspita (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
Digital literacy is needed by students and teachers in schools so that teachers and students can take advantage of rapidly developing technology. Using digital learning resources with the right media will be able to create effective teaching and learning activities and foster enthusiasm for students. This research aims to describe the use of digital learning resources in increasing students' digital literacy. This research uses a qualitative research method with a descriptive analysis approach design. The results of this research are that the teacher has succeeded in increasing digital literacy in class VII students at MTs Mafatihul Huda through digital learning resources in the form of learning video media, and with digital learning resources, the teacher has succeeded in finding solutions to student problems regarding learning resources that can inspire students' enthusiasm for learning. By increasing digital literacy in class VII, students can answer questions about the problems that exist in society that often occur today. Teachers can take advantage of technological advances by using digital learning resources.